The In vitro Antibiotic Tolerant Persister Population in Burkholderia pseudomallei is Altered by Environmental Factors - Nierman, William C.; Yu, Yan; Losada, Liliana (Frontiers in Microbiology, 2015)
Bacterial persistence due to antibiotic tolerance is a critical aspect of antibiotic treatment failure, disease latency, and chronic or reemergent infections. The levels of persisters is especially notable for the opportunistic Gram-negative pathogens from the Burkholderia and Pseudomonas genera. We examined the rate of drug tolerant persisters in Burkholderia pseudomallei, Burkholderia thailandensis, Burkholderia cepacia complex organisms, and Pseudomonas aeruginosa at mid-log growth in LB broth culture. We found that a fraction of the antibiotic-sensitive cells from every species were tolerant to a 24 hour high-dose antibiotic challenge. All tested Burkholderia strains demonstrated a drug tolerant persister population at a rate that was at least 100 – 500 times higher than P. aeruginosa. When challenged with a 10X minimum inhibitory concentration 24 hour exposure to five different antibiotics with different modes of action we found that in B. pseudomallei Bp82 the same fraction of persisters in the bacterial population was revealed when using 4 of them. This observation suggests that our assay is detecting a single homogeneous persister population. Persistence in B. pseudomallei Bp82 was highly dependent on growth stage, with a surprisingly high persister fraction of >64% of the late stationary phase cells being antibiotic tolerant. Adaptation of B. pseudomallei to distilled water storage resulted in a population of drug tolerant cells up to 100% of the non-drug-challenged viable cell count. Cultivation of B. pseudomallei with a sub-inhibitory concentration of several antibiotics resulted in altered persister fractions within the population relative to cultures lacking the antibiotic. Our study provides insight into the sensitivity of the persister fraction within the population of B. pseudomallei due to environmental variables and suggests a lack of diversity within the persister population.